Volume 4: Ocean Engineering; Offshore Renewable Energy 2008
DOI: 10.1115/omae2008-57396
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study Into Vortex Induced Motion Response of Semi Submersibles With Square Columns

Abstract: Vortex Induced Motion (VIM) of a Deep Draft Semi® with four square columns has been observed in model tests and in a prototype configuration. The flow field around the columns causes the vessel to oscillate along one of the vessel’s main diagonals under particular conditions. The observations and conclusions of three series of VIM model programs are combined in this report. Each test program was executed with a unique objective in mind and each setup was unique. Many similarities in response characteristics ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Most of the corner shape studies were focused on the 0 degree incidence. However, for square section shaped multi-columns structures, the most severe transverse motion which was induced by vortex shedding occurred at 45 degree incidence which was confirmed in both filed measurements and model tests [6][7][8][9][10][11][12]. Thus, the present numerical investigation about corner shape effects is focused on 45 degree incidence.…”
Section: Introductionmentioning
confidence: 63%
“…Most of the corner shape studies were focused on the 0 degree incidence. However, for square section shaped multi-columns structures, the most severe transverse motion which was induced by vortex shedding occurred at 45 degree incidence which was confirmed in both filed measurements and model tests [6][7][8][9][10][11][12]. Thus, the present numerical investigation about corner shape effects is focused on 45 degree incidence.…”
Section: Introductionmentioning
confidence: 63%
“…Although the test was not specifically for the VIM of the DDS model, it was observed that a DDS with deeper draft experiences more significant VIM with predictable oscillation period and the VIM amplitude in strong current tends to be larger than that for the combination of currents and waves. Rijken and Leverette (2008) experimentally investigated the VIM responses of a DDS in the presence of a fatigue sea state and supported by a system with increased sway damping, which delayed the onset of VIM to a higher reduced velocity. Additionally, Rijken et al (2011) analyzed the effects of a SCR system and hull appurtenances on the VIM behavior of a DDS with square columns and observed the differences in VIM response between model tests and field observations.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, as explained in Rijken and Leverette (2008) Reynolds number is still crucial in determining the other viscous effects i.e. drag load.…”
Section: Introductionmentioning
confidence: 99%
“…Their study explicitly showed the effect of the metacentric height of the rig on the motion responses of the platform. As clearly explained in Rijken and Leverette (2008), the crucial parameters determining the VIM responses in tank tests are the reduced velocity, Froude and Reynolds numbers. Of the three parameters, the reduced velocity is the most critical one which is used to assess the experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation